RE-ACTUALIZATION SIRI’ NA PACCE’ CULTURE THROUGH SECTOR COLLABORATION WITH PENTA HELIX MODEL - Bryan Habib Gautama; Muhammad Ripurio; Ghea Rahmayanti (Lafadz Jaya Publisher, 2023)
Siri' na pacce' has lived, developed, and is believed to be a cultural value of the people of South Sulawesi. Siri' na pacce' culture has an important role in maintaining civil society. In society, there is a growing perception that this culture is starting to be abandoned and forgotten due to deviations that occur and external influences that eliminate its existence. This research aims to identify efforts to preserve siri' na pacce' culture through re-actualization, based on considerations such as supporting and inhibiting factors, culture dynamics, development trends, and the sense of urgency. This research uses a qualitative methodology and library research. Re-actualization is carried out with a collaborative approach between various parties using the penta helix model. Based on the analysis, siri' na pacce' has an important role in building community knowledge so it needs to be preserved. Preservation efforts are carried out by re-actualization by involving the government as a regulator, academics acting as drafters, business actors as presenters of economic markets with community participation, the community as intermediaries, providing input, and maintaining cultural values, and the media as a means of promotion to carry out preservation efforts.